Case Report: An incidentally discovered HPV-associated endocervical adenocarcinoma presenting as pseudomyxoma peritonei - Chen, Lijun; Sun, Lin (Frontiers in Oncology, 2026)
This case report describes a 48-year-old woman with occult HPV-associated endocervical adenocarcinoma (Silva pattern B) presenting as bilateral ovarian metastases and pseudomyxoma peritonei–like gelatinous ascites, despite normal cervical morphology and resolved HPV type 45 infection. Initial misdiagnosis as primary ovarian mucinous carcinoma was revised based on histopathology and immunohistochemistry (diffuse p16 positivity, ER-negative and PR-negative, Ki-67 index of 95%), confirming metastatic endocervical adenocarcinoma. The absence of appendiceal lesions excluded true PMP, attributing ascites to tumor mucin secretion. This case highlights the diagnostic challenges of occult cervical adenocarcinoma mimicking PMP and underscores the critical role of immunohistochemical profiling (p16, PAX8, WT1) to differentiate metastatic from primary ovarian tumors. The study emphasizes a multidisciplinary approach for accurate classification of mucinous neoplasms and raises awareness of rare metastatic pathways, such as transtubal dissemination, in HPV-associated cervical adenocarcinoma.